Actualización sobre los virus que infectan papaya en Argentina - Cabrera Mederos, Dariel; Portal, O.; Acuña, Luis Eduardo; Badaracco, Alejandra; Rodríguez, E.; Nickel, A.; Sáez, S.; Nome Docampo, Claudia; Debat, Humberto Julio; Torres, C.; Jaramillo, M.; Trucco, Veronica Milagros; et al. (Asociación Argentina de Fitopatólogos, 2021)
Poster